Hindu book of editorials 2021 - Suresh Nambath (Chennai THG publishing private limited, 2023)
The Hindu Book of Editorials 2021 brings to the reader a selection from the editorial pages of India$1 (Bs national newspaper, The Hindu, offering a recap on the year that went by.Covering topics ranging from politics, governance and civil society, to media, health and education, The Hindu Book of Editorials 2021 offers the reader a perspective of the year in a quick read. This volume, part of a series, is segregated topic-wise for ease of reading.s
Keywords: Hindu